Marketing Factors Affecting Parental Satisfaction in the Bus ServicePick-up and Drop-off Students of a Private School in Logistics - สงสม, ศุภเดช; อภิธานวิทิต, ธนวัฒน์; เอี่ยมลาภะ, จุลจักร (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The research on marketing factors affecting parents' satisfaction with the school bus service of a private school in logistics has the following objectives: 1) to study the level of satisfaction with the school bus service of a private school classified by demographic factors; 2) to study and compare service quality factors affecting satisfaction with the school bus service; and 3) to study the relationship between service quality factors and satisfaction with the school bus service of a private school. The research instruments used were questionnaires, random sampling without considering the probability, and convenient sampling. The sample group used in this research was 400 parents of students who used the school bus service of a private school. The sample size was determined by the Taro Yamane method using a simple random sampling method. The statistics used in the research were percentage, mean, and standard deviation. The hypothesis was tested using the Independent Sample Test, One-way ANOVA, and pairwise comparison analysis using the LSD (Post Hoc) method. The results of the research found that most of them were males more than females. Most of them worked as employees of private companies, had an income of 15,001-25,000 baht, and often chose to use the school bus service of a private school. The majority of respondents often do not have enough time to travel to send their children to a private school and are concerned about their children's safety when using the school's shuttle bus service.